Saline Experimental Range Dormant Season Wildfire: Short-Term Effect on Forage Production and Plant Composition - Keith R. Harmoney (Kansas Agricultural Experiment Station Research Reports, 2020)
Rangeland wildfires in the southern plains may occur any time of year, but the low humidity, increasing temperatures, and dry and abundant fuel load of late winter and early spring can result in greater wildfire occurrence and severity. Fires that occur before the growing season remove standing residual vegetation and greatly reduce litter cover, so the soil surface may be left bare for several weeks or months before the onset of new pasture growth. Exposure of plant buds to cold temperatures during dormancy, soil water evaporation, and soil crusting from the force of falling precipitation and puddling may lead to the eventual loss of plant density and available soil moisture for plant growth following wildfire. Information collected from a previous wildfire that occurred during mid-March at the Kansas State University Agricultural Research Center–Hays showed that forage production was significantly reduced for two years following the fire. However, timing and conditions leading up to wildfires and conditions following wildfires may allow pastures to respond to each fire differently. In the week of March 5-11, 2017, several wildfires ignited throughout central and western Kansas. One of those fires was the largest known wildfire in Kansas history, the Starbuck Fire, that consumed more than 460,000 acres of Kansas land in Clark, Meade, and Comanche counties. Another fire ignited on the Kansas State University Saline Experimental Range (SER) in northeast Ellis County on March 7, 2017.
Keywords: bunchgrass; litter cover; rhizomatous species; stoloniferous species